Pengaruh Pengalaman Magang, Kepribadian, dan Pasar Kerja terhadap Pemilihan Karir sebagai Auditor - Handoko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to determine whether internship experience, personality, and job market affect accounting students' career choices as auditors. The research applies quantitative approach, involving data collected through questionnaires. The population includes undergraduate students in Accounting of Universitas Brawijaya, class of 2020, from which the samples amount used of 80 students are selected through purposive sampling utilizing five-point Likert scale. The data are analyzed by multiple linear regression and processed by SPSS software. The research results exhibit that internship experience have a positive effect on accounting students' career choices as auditors, personality have a positive effect on accounting students' career choices as auditors, and job market have a positive effect on accounting students' career choices as auditors. The implications of this research are useful as a reference tool for further research which also examines determining the influence of career auditor selection, a means of understanding public accounting firms to determine the factors driving auditor performance by knowing the basis for selecting auditors, and assisting public accounting firms in creating auditor performance policies at work.